Analysis of family grief members in the context of COVID-19: an integrative review (Research, Society and Development, 2022)
The unique circumstances of deaths amidst a pandemic can negatively affect the loss adaptation of relatives COVID-19 victims, favoring the appearance of disorders related to grief. This study is an integrative review that aimed to present another face of mortality from the disease in order to contribute to the reorganization of care services for family members. Were used as databases MEDLINE via PubMed, Europe PubMed Central, Virtual Health Library and Scientific Electronic Library Online. Were included reports published between 2020-2021. As a result of applying the inclusion and exclusion criteria, 08 studies were selected for bibliometric analysis, methodological topics and content. Studies shown that the characteristic trauma of grief experienced during the pandemic includes multiple deaths, the feeling of helplessness and guilt and the lack of funeral ceremonies. The main results of this review revealed grief related to COVID-19 favors functional impairment contributed functional impairment, in addition to symptoms of pathological grief in the bereaved. The importance of good communication between the health team and family members and the social support found by family members on social networks such as Facebook was also evidenced. It is concluded with the study that the adaptation of families to bereavement had interference of the new circumstances of care and contact with patients imposed by the pandemic.